Urgensi Ketahanan Nasional dan Bela Negara Bagi Bangsa Indonesia - Nopi Nopita Sari; Azhariah Fatya; Sinta Sinta; Bunga Sovia Erik; Amelia Rahmi; Siti Aisyah; Bambang Trisno (Lembaga Pengembangan Kinerja Dosen, 2024)
National resilience is one of the concepts of Indonesian statehood. The resilience of a nation is basically needed to guarantee and strengthen the capability of the nation concerned both in order to maintain its unity, face future threats and seek resources to meet life's needs. The research objective is to determine the urgency and challenges of national resilience and national defense for the Indonesian nation. Research results will be obtained using the Literature review research method, namely a method of collecting library data and information by exploring knowledge or knowledge from sources such as books, journals, written works, lecture notes and several other sources that are related to the research object. The research results show that resilience comes from the word